(untitled) (International Journal of Engineering and Computer Science, 2017)
Data security and access control are the most challenging research work going on, at present, in cloud computing. This is because of the users sending their sensitive data to the cloud providers for acquiring their services. In cloud computing, the data is going to be stored in storage area provided by the service providers. The service providers must have a suitable way to protect their client’s sensitive data, especially to protect the data from unauthorized access. A common method of information privacy protection is to store the client’s data in encrypted form. If the cloud system is responsible for both storage and encryption/decryption of the data, the system administrators may simultaneously obtain encrypted data and the decryption keys. This will allow them to access the information of the client without any authorization. This leads to the risk of sensitive information leak and the method involved of storage and encryption/decryption is costly too. Hence, to overcome these problems, a model (cloud server) has been proposed in this paper which accepts only those data which are required in an encoded form, performs the service opted by the client and sends the result in the encoded format to be understood by the respective client.